If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6 + -9x) = 0 (6 * 7 + -9x * 7) = 0 (42 + -63x) = 0 Solving 42 + -63x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -63x = 0 + -42 Combine like terms: 42 + -42 = 0 0 + -63x = 0 + -42 -63x = 0 + -42 Combine like terms: 0 + -42 = -42 -63x = -42 Divide each side by '-63'. x = 0.6666666667 Simplifying x = 0.6666666667
| -7(x-3)= | | x^2+8=-3x^2+5 | | 21x-70=3.5 | | 4x^2+35x+75=0 | | (2x-8)(x-3)=0 | | 36=-9k | | 4k+h=-2-14 | | b-4=-1 | | x^2+25x+24= | | 15-4(x+1)=10 | | 85w=76w-27 | | (3x+5)/2=-7 | | 3(8-d)-48=27d-6(4+5d) | | 6(c+7)-20=6c | | 49.50x=42916.5 | | 49.50x=321750 | | ln(7.28)=0 | | 3m-16=2(4m-5) | | (4f-5)6=26 | | -(8x+4)=4x-2(6x+2) | | 2-x+3=-(x-1) | | 0.15x=4.5 | | 0.15x=7.2 | | 4(4-3x)=4x+6 | | .10-15=21 | | -4x+6=-2(-3x+9) | | 3x+6-2=x+14 | | 3(x-5)+5+2=4(x+4)+5 | | 3r^2-26r+48=0 | | 3x-36=5x-145 | | 19=3a | | 3x+7=14+4x |